ANALYSIS OF THE PRELIMINARY DESIGN OF A METHYL CHLORIDE CHEMICAL PLANT VIA THE REACTION OF METHANOL AND HYDROGEN CHLORIDE WITH A PRODUCTION CAPACITY OF 45,000 TONS PER YEAR - Wicaksono, Dimas Satrio (Journal of Vocational Studies on Applied Research, 2025)
The increasing demand for chemical intermediates in the national chemical industry highlights the need for domestic production to reduce reliance on imports, particularly for strategic products such as methyl chloride. This study presents a preliminary design of a methyl chloride chemical plant with a production capacity of 45,000 tons per year using methanol and hydrogen chloride as raw materials through a catalytic gas-phase synthesis process. The analysis includes mass and energy balance calculations, determination of major equipment specifications, and evaluation of process utility requirements. Furthermore, Pinch Technology Analysis is applied to optimize energy integration within the process by designing an efficient Heat Exchanger Network (HEN). The results indicate that the proposed process is technically feasible and capable of meeting product specifications while significantly reducing external utility consumption through effective internal heat recovery. The integration of preliminary plant design and Pinch Analysis demonstrates strong potential for improving energy efficiency and lowering operational costs, providing a solid basis for further detailed engineering and economic evaluation.